2016
DOI: 10.1016/j.asr.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cost mission design using surrogate models

Abstract: This paper uses surrogate models to reduce the computational cost associated with spacecraft mission design in three-body dynamical systems. Sampling-based least squares regression is used to project the system response onto a set of orthogonal bases, providing a representation of the ∆V required for rendezvous as a reduced-order surrogate model. Models are presented for mid-field rendezvous of spacecraft in orbits in the Earth-Moon circular restricted three-body problem, including a halo orbit about the Earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Peng and Wang proposed a dynamic metamodel-based optimization method for spacecraft formation reconfiguration on liberation point orbits to achieve fast path planning [182]. Feldhacker et al investigated a samplingbased least-squares regression method to optimize the required velocity increments for rendezvous in spacecraft three-body dynamical systems [183]. Peng et al proposed an adaptive metamodel-based optimization method called the sequential radial basis function for satellite truss structure optimization [184].…”
Section: Satellite Constellation Mdo Problemmentioning
confidence: 99%
“…Peng and Wang proposed a dynamic metamodel-based optimization method for spacecraft formation reconfiguration on liberation point orbits to achieve fast path planning [182]. Feldhacker et al investigated a samplingbased least-squares regression method to optimize the required velocity increments for rendezvous in spacecraft three-body dynamical systems [183]. Peng et al proposed an adaptive metamodel-based optimization method called the sequential radial basis function for satellite truss structure optimization [184].…”
Section: Satellite Constellation Mdo Problemmentioning
confidence: 99%
“…Additionally, surrogate models (SM) are used for representing nonlinearity of hydrodynamic problems [9]. Therefore, SM, also so-called low fidelity models, are becoming popular [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…SM are successfully used by various researches to optimize wind turbine performance [11][12]. These authors reported that SM are very efficient in comparison with the conventional optimization methods [11][12]. However, the optimization of multi-element hydrofoils for hydrokinetic turbines using SM has not been employed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Meantime, these urgent transfer missions truly exist when the spacecraft meets emergency incidents or temporary missions.For example, in pursuit and capturemissions [16][17][18][19], when a spacecraft needs to pursue or intercept anobjective spacecraft that flies in other orbits, the transfer maneuver opportunity is significant. In the near future, some space stations or telescopes may locate on halo orbits of the Sun-Earth/Earth-Moon systems.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the efficiency for on-line designing optimal transfer trajectory has significant value. Furthermore, according to the point of view in thereference [19], the use of as efficient design tool can enable significant time savings when performing in trajectory design over long propagation times, trajectory optimization using massive grid searches, or trade space exploration for exercises in rapid mission design.Based on the above analysis, the main concern of this paper is to find a fast multi-objective design method for transfer trajectory.Besides, a popular tool for constructing the fast optimization method is surrogate model [20][21][22][23][24][25].Thus, an adaptive surrogate model basedmulti-objective optimization method is proposed in this paper.…”
Section: Introductionmentioning
confidence: 99%